Profiles of mental health help seeking among Australian adolescent males. (October 2021) - Liddle, Sarah K.; Robinson, Laura; Vella, Stewart A.; Deane, Frank P.
Abstract: Introduction: Adolescent males are at increased risk of mental illness and are reluctant to engage in treatment. This study aims to identify subgroups of help-seeking intentions among a sample of Australian male adolescents. Methods: A sample of 1038 male adolescent sport participants in Australia (age M = 14.69 years, SD = 1.35) reported help-seeking intentions from ten sources and from 'no one'. Latent profile analysis was conducted based on these 11 items. Identified profiles were then compared across mental health measures. Results: Four latent profiles were identified: Low general help-seekers (10.5%), Moderate general help-seekers (46.8%), High general help-seekers (25.5%), High family and friends help-seekers (17.2%). Low, Moderate, and High general help-seekers had uniformly low, moderate, and high intentions to seek help from all sources, respectively. High family and friends help-seekers reported high endorsement of intentions to seek help from intimate partners, friends, parents, and other relatives, but low intentions for other sources. Low general help-seekers had lower intentions to seek help from parents compared to all other profiles. They also had significantly lower perceived family support and higher psychological distress. Conclusions: Low general help-seekers were particularly reluctant to seek help from all sources and at high risk of experiencing psychological difficulties. Their distinct profile offers potential to identify this high-risk group through the use of ratings on the parent help-seeking intentions item. Further research should investigate the predictive utility of this item on help-seeking and mental health, and should consider the influence of masculinity and previous experiences of help-seeking.